Fatigue strength assessment of laser stake‐welded T‐joints subjected to reversed bending. Issue 10 (1st April 2016) - Frank, D.; Dissel, P.; Remes, H.; Romanoff, J.; Klostermann, O.
Abstract: The paper investigates the fatigue strength of laser stake‐welded T‐joints subjected to reversed bending. The fatigue tests are carried out with the load ratio, R  ≈ −0.8. The experimental data is firstly analysed using the nominal stress approach and then by the J ‐integral as the local fatigue strength parameter in the finite element (FE) assessment. The nominal stress approach demonstrated that the fatigue strength of the investigated T‐joints is lower than encountered for any other steel joint under reversed tensile loading. The results also showed that the fatigue strength of this joint under the load ratio R  ≈ −0.8 increases with respect to R  = 0 bending by 22.6% in the case of the nominal stress approach and 13% in the case of the J ‐integral approach. However, the slopes of the fatigue resistance curves for different load ratios appear very similar, suggesting that the load ratio has an insignificant influence to the slope. In contrast to the similar slopes, the scatter indexes were different. The nominal stress approach shows that the scatter index is 3.4 times larger for R  ≈ −0.8 than R  = 0 bending. The J ‐integral approach showed that the scatter index for R  ≈ −0.8 is only 67% larger than in the R  = 0 case because the weld geometry is modelled in the FE analysis.